2018
DOI: 10.18196/ijnp.2284
|View full text |Cite
|
Sign up to set email alerts
|

Perangkat Kesiapsiagaan Bencana Untuk Wanita Hamil dan Pasca Melahirkan

Abstract: Letusan gunung berapi pada tahun 2010 meningkatkan kesadaran akan kebutuhan untuk mendidik populasi rentan dalam kesiapsiagaan bencana. Wanita dan bayinya teruta ma berisiko terkena bahaya karena bencana alam. Penelitian saa t ini menunjukkan bahwa populasi rentan biasa nya kurang siap untuk kejadian bencana besar. Tujuan: Tujuan dari penelitian ini adalah untuk mengetahui efektivitas dari intervensi pendidikan singkat yang ditujukan untuk meningkatkan tingkat kesiapsiagaan bencana dari wanita hamil da n pasca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 2 publications
0
1
0
Order By: Relevance
“…Research has found a significant difference in pre-test and post-test scores of disaster preparedness among women who received a short educational intervention. The post-test scores were significantly higher than the pre-test scores, indicating that the intervention successfully increased pregnant women's preparedness for disasters (14).…”
Section: Introductionmentioning
confidence: 78%
“…Research has found a significant difference in pre-test and post-test scores of disaster preparedness among women who received a short educational intervention. The post-test scores were significantly higher than the pre-test scores, indicating that the intervention successfully increased pregnant women's preparedness for disasters (14).…”
Section: Introductionmentioning
confidence: 78%